Humanisme dalam Filsafat Pendidikan Islam: Telaah Atas Peran Manusia Sebagai Khalifah - Rizqi Nur Amalya; Abdul Kobir; Muhammad Nur Ilham; M. Iqodzul Himam Abil Izz (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study elaborates on the concept of humanism in Islamic educational philosophy by highlighting in greater depth the role of humans as caliphs on earth. Humanism from an Islamic perspective not only focuses on humans as rational beings but also emphasizes the moral, spiritual, and social responsibilities inherent in the mandate of the caliphate. This study applies a qualitative approach with a literature study, where data is obtained from various written sources such as scientific articles and academic publications that discuss humanism in Islamic education and the concept of the human caliphate. The data collection process is carried out through searching, selecting, and organizing literature relevant to the focus of the study. The collected data are then analyzed using descriptive-qualitative techniques through the stages of simplifying information, grouping findings, and formulating systematic conclusions. The results of the study indicate that the position of humans as caliphs requires the development of intellectual, ethical, and spiritual potential in an integrated manner in the educational process. Therefore, Islamic education needs to be directed towards a holistic humanization process, which not only strengthens reasoning and social character but also fosters a transcendental awareness of human relationships with God, fellow humans, and nature. Thus, humanism in Islamic education is not secular, liberal, or anthropocentric, but is firmly rooted in divine values ​​that harmoniously unite the divine and human dimensions.